Methylation profiling of choroid plexus tumors reveals 3 clinically distinct subgroups - Thomas, Christian; Korshunov, Andrey; Jones, David T. W.; Deimling, Andreas von; Pfister, Stefan; Capper, David (Neuro-Oncology, 2016)
Abstract Background. Choroid plexus tumors are intraventricular neoplasms derived from the choroid plexus epithelium. A better knowledge of molecular factors in
Gesehen am 05.09.2019